Trace‐level screening of dichlorophenols in processed dairy milk by headspace gas chromatography. Issue 20 (27th September 2016) - Gras, Kaelyn; Luong, Jim; Gras, Ronda; Shellie, Robert A.
Abstract : A headspace gas chromatographic approach based on flame ionization detection has been successfully developed for the determination of parts‐per‐billion levels of 2, 4‐dichlorophenol and 2, 6‐dichlorophenol in processed dairy milk. Under the right environmental conditions, these compounds are produced as products of the reductive dechlorination of pentachlorophenol. Maintaining a highly inert chromatographic system and employing a recently commercialized inert capillary column permits the analysis of 2, 4‐dichlorophenol and 2, 6‐dichlorophenol without derivatization. Further, a detection limit improvement of more than a factor of two was achieved by adding sodium sulfate to substantially decrease the solute partition coefficient in the matrix. A detection limit of 1 ng/g and a limit of quantitation of 2 ng/g were attained, and complete analysis can be conducted in < 13 min. Reproducibility of area counts over a range from 20 to 200 ng/g and over a period of 2 days were found to be less than 6% ( n = 20). A linear range from 5 to 500 ng/g with a correlation coefficient of at least 0.9992 was obtained for 2, 4‐dichlorophenol and 2, 6‐dichlorophenol. Spike recoveries from 10 to 500 ng/g for all the analytes range from 92 to 102%.